Observations de pratiques de professeurs-stagiaires. Quelles évolutions des savoirs professionnels ? - Alain Jean (Recherches en Éducation)
The training of the teachers underwent numerous reforms these last years. The observation of the student teachers’ practices, through the activity which they mobilize in situation of class, could allow to detect professional knowledges in elaboration or stabilization. This article give some results of a longitudinal research led in 2011, which consisted in observing student teachers’ practices during a school year. Video recordings of class and autoconfrontations were regularly led with three student teachers during their year of training in responsibility of class. In a more precise way, our question of research concerned the evolutions of the observable practices. What forms can take these evolutions of practices, which typifies of a possible professional development bound to these evolutions at the teachers trainees in situations of responsibility of class? What elements build these practices? What type of professional development builds itself for the student teachers? A review of literature on the professional knowledges allowed us to develop our conception of this concept. The article centers on the professional knowledges mobilized by these novice teachers and on their evolution during the school year.